Stereodynamical control of a quantum scattering resonance in cold molecular collisions - Jambrina, PG; Croft, JFE; Guo, H; Brouard, M; Balakrishnan, N; Aoiz, FJ (American Physical Society, 2019)
Cold collisions of light molecules are often dominated by a single partial wave resonance. For the rotational quenching of HD (v = 1, j = 2) by collisions with ground state para-H2, the process is dominated by a single L = 2 partial wave resonance centered around 0.1 K. Here, we show that this resonance can be switched on or off simply by appropriate alignment of the HD rotational angular momentum relative to the initial velocity vector, thereby enabling complete control of the collision outcome.